2020
DOI: 10.3390/s20216085
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth Subcarbonate Decorated Reduced Graphene Oxide Nanocomposite for the Sensitive Stripping Voltammetry Analysis of Pb(II) and Cd(II) in Water

Abstract: In this paper, bismuth subcarbonate (BiO)2CO3-reduced graphene oxide nanocomposite incorporated in Nafion matrix ((BiO)2CO3-rGO-Nafion) was synthesized and further applied, for the first time, in the sensitive detection of Pb(II) and Cd(II) by square-wave anodic stripping voltammetry (SWASV). The as-synthesized nanocomposites were characterized by energy-dispersive spectroscopy (EDS), Raman spectroscopy, scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 49 publications
3
22
0
Order By: Relevance
“…EIS was used to explore the material/electrode interface properties and changes based on the impedance changes ( Figure S2B ). The EIS results show different semicircles, each with a diameter equivalent to the charge transfer resistance (R ct ), which corresponds to the process of electron transfer limitation [ 47 , 48 , 49 ]. Based on the value of semicircle diameter, the order of the R ct of different modified electrodes was as follows: Fe 3 O 4 /GCE (curve b) > Fe 3 O 4 -Au/GCE (curve c) > Fe 3 O 4 -Au-IL/GCE > bare GCE (curve a).…”
Section: Resultsmentioning
confidence: 99%
“…EIS was used to explore the material/electrode interface properties and changes based on the impedance changes ( Figure S2B ). The EIS results show different semicircles, each with a diameter equivalent to the charge transfer resistance (R ct ), which corresponds to the process of electron transfer limitation [ 47 , 48 , 49 ]. Based on the value of semicircle diameter, the order of the R ct of different modified electrodes was as follows: Fe 3 O 4 /GCE (curve b) > Fe 3 O 4 -Au/GCE (curve c) > Fe 3 O 4 -Au-IL/GCE > bare GCE (curve a).…”
Section: Resultsmentioning
confidence: 99%
“…The (BiO) 2 CO 3 -rGO-Nafion and Fe 3 O 4 -Au-IL sensing nanocomposites were synthesized based on previously reported protocols ( Zhao et al, 2020 ; Sedki et al, 2021 ) using the following steps.…”
Section: Methodsmentioning
confidence: 99%
“…The employment of the disposable SPEs avoided the traditional pretreatment process frequently-used to prepare glassy carbon or carbon paste WE, but obtained a comparable sensitivity based on the modification of the nanocomposites. Compared to the batch electrochemical cells in previously published papers, including ours (Zhao et al, 2020;Sedki et al, 2021), the flow electrochemical stripping analysis reported in this study has the advantages of: automation potential, high throughput analysis of large quantities of samples, high reliability due to reduced human intervention, miniaturization potential on the size of analytical cell/device, near-/real-time detection, integration with other analytical systems and capability for the simultaneous detection of As(III), Cd(II), and Pb(II). Additionally, the flow cell geometry was optimized and finally confirmed by COMSOL Multiphysics to resolve the problems existing in the application of SPEs in flow system based on a finite element method (FEM), which is a reliable and effective approach for the computational fluid dynamic (CFD) analysis.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations